Contribution of Serological Rapid Diagnostic Tests to the Strategy of Contact Tracing in Households Following SARS-CoV-2 Infection Diagnosis in Children - Charbonnier, Lorelei; Rouprêt-Serzec, Julie; Caseris, Marion; Danse, Marion; Cointe, Aurélie; Cohen, Laure; Faye, Albert; Ouldali, Naïm; Gaschignard, Jean (Frontiers in Pediatrics, 2021)
BACKGROUND: The contact-tracing and isolation of contagious individuals are cornerstones in the control of the COVID-19 pandemic. Strategies to identify household contacts that should be isolated around index children tested positive for SARS-CoV-2 remain to be clarified. We aimed to compare contact-tracing strategies around an index child positive for SARS-CoV-2 using serological Rapid Diagnostic Tests (RDT). METHODS: We conducted a contact-tracing study in households of index cases children in the Paris region, France, between May 8 and July 27, 2020. We compared two strategies, one using SARS-CoV-2 Reverse Transcriptase Polymerase Chain Reaction (RT-PCR), one combining RT-PCR and serological RDT. The contacts RT-PCR-/RDT+ were considered to have been previously infected and not requiring isolation. The primary outcome was the proportion of contacts that could avoid quarantine with the two screening strategies. RESULTS: We included 34 children as index cases. Median age was 7 years. They generated 184 contacts (111 adults, 73 children) tested by RT-PCR: 24/184 (13%) were positive. The strategy combining RDT and RT-PCR was performed in 120/184 contacts (77 adults, 43 children) of 26 index children: 16/120 (13%) were RT-PCR+ and 47/120 (39%) were RDT+. Among the 16 individuals RT-PCR+, 14 (87%) were also RDT+. Among the 104 individuals RT-PCR-, 33 were RDT+. Hence 33/120 (27%) individuals were not isolated. CONCLUSIONS: Following the diagnosis of SARS-Cov2 infection in children a strategy combining serological RDT and nasopharyngeal RT-PCR enabled us to identify around one fourth of contacts with past infection and avoid unnecessary isolation of these individuals.